Identification and in vitro control of rice sheath rot disease associated with grains discoloration in Merlimau, Melaka using crude weed extract / Nurul Nadia Rahim - Rahim, Nurul Nadia (Faculty of Plantation and Agrotechnology, 2018)
Rice is one of the most important grains which highly in calories consumed by people all around the world and contributes to many aspects such as in economics and social fields in Asia. More than 90% of rice is produced and consumed by 60% of the people worldwide. The spread of sheath rot disease caused by Sarocladium oryzae has become a problem because it is difficult to eradicate and needs to take proper control methods to eliminate the disease. Therefore, the main objectives of this study were to screen the antifungal activity for eight weed extracts used in the study against Sacloradium oryzae caused sheath rod disease on rice in vitro and in vivo studies which have antifungal activity against sheath rot disease in paddy. Next, to determine the most effective weed extracts against sheath rot disease. In this study, eight types of weeds named ST, NB, MC, ET, MG, CO, AC and CM were randomly to determine its antifungal activity against sheath rot disease on PDA. In vitro studies, Sacloradium oryzae was placed in the PDA amended with weed extracts. The less mycelia growth diameters for this antifungal activity were ST, MC and MG respectively at about 0.8333 cm, 1.3667 cm and 1.0667 cm respectively. This study proven the effectiveness of weed extract called ST, MC and MG against Sacloradium oryzae using food poisoning technique in vitro studies. In vivo studies, sheath rot disease caused by Sacloradium oryzae was inoculated on healthy grains to fulfill the Koch postulate’s rules. The data obtained in vitro studies were analyzed using ANOVA in SPSS software. The results showed that weed extract called ST, MC and MG have a high efficacy rate in terms of reducing the mycelia growth compared to other weeds tested in this studies.